The Influence of Problem Based Learning (PBL) Models Integrated Information Communication and Technology (ICT) on Mental Models in Primary School Science Learning - Karnilawati; Yanti Fitria; Darmansyah Darmansyah; Zelhendri Zen (Postgraduate, University of Mataram, 2023)
The purpose of this study is to examine the impact of the ICT integrated problem-based learning paradigm on elementary school students' mental models. When learning is done using ICT and PBL models, it will be observed if elementary school pupils' mental models grow or shrink.This study used an experimental, quantitative research design with a nonequivalent control group. 25 pupils participated in this study at SDN 08 Kampung Jawa 1 in Pariaman. The multiple choice questions used in this research tool are tests. The independent sample t-test was used in this study's data analysis. It is required to assess the conditions for data analysis, particularly the normality and homogeneity tests, before the data is studied. Based on the study's findings, a significance value (2-tailed) of 0.001 0.05 was found, leading to the conclusion that Ho is rejected and Ha is accepted, indicating that the PBL learning model's integration with ICT had a significant impact on elementary school students' mental models.